Supporting Reaching Movements of Robotic Hands Subject to Communication Delay by Displaying End Effector Position Using Three Orthogonal Rays - Chinen, Akihito; Hoshino, Kiyoshi (Journal of robotics and mechatronics, 2017)
In this paper, we propose an operation support system, which shows the spatial relation between a robotic hand and an object, to overcome reduced usability due to communication delay. A communication delay of four seconds occurs during remote operation between the earth and the moon. Previous studies have used a method that feeds back the predicted position of a robotic hand after the communication delay occurs. However, this does not allow an accurate reaching motion necessary for grasping. Therefore, we try to show the spatial relation between a robotic hand and an object using three orthogonal rays, where each is annotated with 1 cm increments. Based on the results of our experiments, the grasping success rate of the proposed method increases by three times. As a result, the proposed method is effective in making accurate reaching motions for grasping in the visual-servoing remote control between the earth and the moon.